Critical Regionalism in Indonesian International-Standard Sports Facilities: Architectural Identity and Resilience - Dimas Pradipta; Darmansjah Tjahja Prakasa; Ibrahim Tohar (Greenation Research & Yayasan Global Resarch National, 2026)
The development of internationally standardized sports facilities in Indonesia often adopts uniform global design standards to meet international federation requirements, risking the loss of Nusantara architectural identity and limiting adaptation to tropical climates and long-term operational needs. This study formulates a critical regionalism strategy for planning internationally standardized sports facilities that integrates Nusantara architectural identity with architectural resilience. A qualitative comparative multiple-case study was conducted on three facilities: the Mandalika International Street Circuit in Lombok, the Muncar BMX Circuit in Banyuwangi, and Manahan Stadium in Surakarta. The analysis focused on contextual typo-morphology, regionalist tectonic strategies, and spatial resilience. The findings reveal three key strategies: integrating site topography and geo-climatic conditions into massing and track design, translating cosmological values and vernacular typologies into contemporary tectonic expressions rather than decorative forms, and creating loose-fit spaces that support flexible post-event functions for long-term economic and social sustainability. Architectural resilience is strengthened through tropical climate-responsive design, adaptable circulation systems, and community participation in post-construction management. This study contributes a cross-typology analytical framework that integrates critical regionalism, Nusantara architectural identity, and architectural resilience, offering a comprehensive reference for planning internationally standardized sports facilities in Indonesia.